2013
DOI: 10.1371/journal.pone.0071672
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic and Autophagic Effects of Sesbania grandiflora Flowers in Human Leukemic Cells

Abstract: BackgroundIdentification of cytotoxic compounds that induce apoptosis has been the mainstay of anti-cancer therapeutics for several decades. In recent years, focus has shifted to inducing multiple modes of cell death coupled with reduced systemic toxicity. The plant Sesbania grandiflora is widely used in Indian traditional medicine for the treatment of a broad spectrum of diseases. This encouraged us to investigate into the anti-proliferative effect of a fraction (F2) isolated from S. grandiflora flowers in ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 63 publications
1
14
0
Order By: Relevance
“…B and it is seen that the model is statistically relevant ( R 2 = 0.85, RMSE = 5.75) (Fig. B) . It is expected that the main product would exhibit antiproliferation on the fibroblast cells and this is consistent with the prediction of the model.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…B and it is seen that the model is statistically relevant ( R 2 = 0.85, RMSE = 5.75) (Fig. B) . It is expected that the main product would exhibit antiproliferation on the fibroblast cells and this is consistent with the prediction of the model.…”
Section: Resultssupporting
confidence: 73%
“…However, not all of these variants impacted the proliferation activity of the cells. Therefore, the variants exhibiting significant effect based on the abundance, sensitivity in terms of their ability to cause change in proliferative activity per unit change in percentage variant, or both were selected to build a refined model as per the procedure outlined in . In the refined model, the significance of the parameters was determined based on p ‐values ( p < 0.0001) and F value (ratio of mean square of the model to the mean square of the error).…”
Section: Methodsmentioning
confidence: 99%
“…The inhibitory effect of EO on cancer cells via induction of apoptosis was further confirmed by Hoechst 33258 staining. Live cells with homogeneous light blue nuclei could be observed under fluorescence microscopy after staining with Hoechst 33258, and the apoptotic cells displayed bright blue due to karyopyknosis and chromatin condensation after treating with Hoechst 33258, and the nuclei of dead cells could not be stained (Roy et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Plants contain a huge range of active compounds with the most abundant being polyphenols, carotenoids, vitamin (vitamin A, C, riboflavin, nicotinic acid), and minerals like zinc and selenium which form an integral part of antioxidant systems and reduce cellular damages [21,22]. Roy et.al, 2013 reported that a fraction isolated from flowers, preferentially kills leukemic cells (particularly those of histiocyte lymphoma) by triggering programmed cell death [23]. In 4 different studies from 2012 to 2016, it was found that the flower, fruit and the whole plant extract reduced blood glucose, cholesterol, TG and LDL, lipid peroxidation and increased and superoxide dismutase and catalase of insulin and hemoglobin in experimental animals [24][25][26][27].…”
Section: Fig-2: Bok Phool or Heron Flower [2]mentioning
confidence: 99%